2017
DOI: 10.1017/s0954579417001262
|View full text |Cite
|
Sign up to set email alerts
|

Cumulative prenatal exposure to adversity reveals associations with a broad range of neurodevelopmental outcomes that are moderated by a novel, biologically informed polygenetic score based on the serotonin transporter solute carrier family C6, member 4 (SLC6A4) gene expression

Abstract: While many studies focus on the association between early life adversity and the later risk for psychopathology, few simultaneously explore diverse forms of environmental adversity. Moreover, those studies that examined the cumulative impact of early life adversity focus uniquely on postnatal influences. The objective of this study was to focus on the fetal period of development to construct and validate a cumulative prenatal adversity score in relation to a wide range of neurodevelopmental outcomes. We also e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

6
87
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 54 publications
(98 citation statements)
references
References 120 publications
(150 reference statements)
6
87
1
Order By: Relevance
“…38 Serotonin is known to affect the development of brain pathways and networks 44 and, as mentioned previously, childhood trauma dysregulates serotonin neurotransmission. 45 We showed that the serotonin transporter gene expression-based polygenic score significantly interacts with a cumulative prenatal adversity score on measures of childhood cognitive-emotional problems, suggesting again that serotonin function is involved in the long-term effects of prenatal adversity on child socioemotional outcomes. 45 We showed that the serotonin transporter gene expression-based polygenic score significantly interacts with a cumulative prenatal adversity score on measures of childhood cognitive-emotional problems, suggesting again that serotonin function is involved in the long-term effects of prenatal adversity on child socioemotional outcomes.…”
Section: Exploring the Mechanisms Linking Early Life Adversity To Chimentioning
confidence: 72%
See 3 more Smart Citations
“…38 Serotonin is known to affect the development of brain pathways and networks 44 and, as mentioned previously, childhood trauma dysregulates serotonin neurotransmission. 45 We showed that the serotonin transporter gene expression-based polygenic score significantly interacts with a cumulative prenatal adversity score on measures of childhood cognitive-emotional problems, suggesting again that serotonin function is involved in the long-term effects of prenatal adversity on child socioemotional outcomes. 45 We showed that the serotonin transporter gene expression-based polygenic score significantly interacts with a cumulative prenatal adversity score on measures of childhood cognitive-emotional problems, suggesting again that serotonin function is involved in the long-term effects of prenatal adversity on child socioemotional outcomes.…”
Section: Exploring the Mechanisms Linking Early Life Adversity To Chimentioning
confidence: 72%
“…21 We recently created a hippocampal-specific, expression-based polygenic score reflecting variations in the function of the serotonin transporter gene network, using a novel process for genome profiling. 45 We showed that the serotonin transporter gene expression-based polygenic score significantly interacts with a cumulative prenatal adversity score on measures of childhood cognitive-emotional problems, suggesting again that serotonin function is involved in the long-term effects of prenatal adversity on child socioemotional outcomes. 45…”
Section: Exploring the Mechanisms Linking Early Life Adversity To Chimentioning
confidence: 72%
See 2 more Smart Citations
“…Recently in this journal, Silveira et al (2017) sought to determine whether, in the Maternal Adversity, Vulnerability and Neurodevelopment (MAVAN) cohort, prenatal adversity, operationalized using a composite measure of multiple indicators (e.g., maternal health during pregnancy, socioeconomic status), interacted with a biologically informed polygenic index, based on genes coexpressed with the serotonin transporter gene in the hippocampus, in predicting a diverse set of neurodevelopmental outcomes measured at 48 and 60 months. Importantly, functional polymorphisms in the promoter region of the SLC6A4 gene moderate the influence of stressful life events and of positive environmental exposures on the development of and resilience to psychopathology at different ages (Bukh et al, 2009;Caspi et al, 2003;Eley et al, 2004;Kendler, Kuhn, Vittum, Prescott, & Riley, 2005).…”
mentioning
confidence: 99%